An Amorphous Spirobifluorene‐Phosphine‐Oxide Compound as the Balanced n‐Type Host in Bright and Efficient Light‐Emitting Electrochemical Cells with Improved Stability. Issue 7 (25th January 2021) - Tang, Shi; Larsen, Christian; Ràfols‐Ribé, Joan; Wang, Jia; Edman, Ludvig
Abstract: A rational host–guest concept design for the attainment of high efficiency at strong luminance from light‐emitting electrochemical cells (LECs) by suppression of exciton‐polaron quenching [Tang et al., Nature Communications 2017, 8, 1190] has been reported. However, a practical drawback with the presented host–guest LEC devices was that the operational stability is insufficient for many applications. Here, a systematic study is performed, revealing that a major culprit for the limited operational stability is that the employed n‐type host, 1, 3‐bis[2‐(4‐tert‐butylphenyl)‐1, 3, 4‐oxadiazo‐5‐yl]benzene (OXD‐7), has a strong propensity for crystallization and that this crystallization results in a detrimental phase separation of the constituents in the active material during device operation. The authors, therefore, identify an alternative class of concept‐functional n‐type hosts in the form of spirobifluorene‐phosphine‐oxide compounds, and report that the replacement of OXD‐7 with amorphous 2, 7‐bis(diphenylphosphoryl)‐9, 9′‐spirobifluorene results in a much improved operational lifetime of 700 h at >100 cd m −2 during constant‐bias driving at an essentially retained high current efficacy of 37.9 cd A −1 and a strong luminance of 2940 cd m −2 . Abstract : Rationally designed host–guest light‐emitting electrochemical cells can achieve high efficiency at strong luminance but have suffered from poor stability. This study reveals that a major culprit is the propensity of the n‐type host to crystallize, and it addresses this issue through the identification of an amorphous host that results in much‐improved stability at retained high efficiency and luminance.